Profil Literasi Sains Siswa SMP pada materi perubahan iklim - Triska Nuryanti; Indarini Dwi Pursitasari; Bibin Rubini (Postgraduate, University of Mataram, 2023)
This research aims to describe the profile of scientific literacy abilities in science subjects with material on climate change for class VIII students at SMPN 3 Cileungsi. The research was conducted using the ex-post-facto method on 76 respondents. Data collection was carried out using an interview guide sheet and a scientific literacy test which consisted of competency aspects in explaining scientific phenomena, evaluating and designing scientific investigations, and interpreting scientific evidence and data. The scientific literacy data was then analyzed using quantitative descriptive tests. Based on the results obtained, the average scientific literacy score was 31.58% in the low category. The highest level of knowledge was in the low category in 47 respondents with a score of 61.8%, while the highest score was in the 29 respondents with a score of 38.2% in the medium category. The low scientific literacy abilities of students are influenced by several factors such as learning resources that lack scientific literacy coverage, evaluation questions that do not refer to scientific literacy indicators, and digital teaching materials that are able to increase scientific literacy. Based on the data obtained, it can be concluded that students' scientific literacy in climate change material is still relatively low.